+0  
 
0
71
1
avatar

how do i convert y=(8/-3)x-(2/3) into Ax+By=C

Guest Sep 16, 2017
Sort: 

1+0 Answers

 #1
avatar+5241 
+1

Ax + By  =  C

 

Since  C  is alone on one side of the equation, let's first solve for  the "C" in our equation, which is the number that is not being multiplied by a variable:  -(2/3)

 

y  =  (8/-3)x - (2/3)

                                           Subtract  (8/-3)x  from both sides of the equation.

-(8/-3)x + y  =  -(2/3)

                                           -(8/-3)  =  8/3

(8/3)x + y  =  -(2/3)

 

Now....as it is.....  A = 8/3 ,  B = 1 ,  and  C = -2/3  .

But I think you want A, B, and C to be integers. So let's multiply through by  3  to clear the fractions.

 

8x + 3y  =  -2

hectictar  Sep 16, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details